Somatotype hormone levels and physical fitness in elite young soccer players over a two-year monitoring period - Hammami, M. A.; Abderrahman, A. B.; Rhibi, F.; Nebigh, A.; Coppalle, S.; Ravé, G.; Tabka, Z.; Zouhal, H. (Journal of Sports Science & Medicine, 2018)
The effect of two soccer-training seasons on the growth, development and somatotype hormone concentrations of elite youth soccer players were evaluated. Eighteen elite soccer players and 18 age-matched non-athletic control subjects participated in the study. Anthropometric-measurements, aerobic and anaerobic performance tests and serum concentrations of insulin-like growth factor-1 (IGF-1), insulin-like growth factor binding protein-3 (IGFBP-3), and growth hormone (GH) were assessed at 5 time points across two competitive seasons. Soccer players revealed higher GH, IGF-1 and IGFBP-3 than the control group across all-time points. Significant moderate correlations were observed only in soccer players between hormonal concentrations (IGF-1 and IGFBP-3) and the jumping tests (r = 0.45-0.48; p < 0.01). Somatotropic axis hormones, anthropometric and physical parameters increased to a greater degree with growth and soccer training combined compared to growth alone. Results from this investigation revealed that intense training did not impair growth or development in these young soccer players across 2-year period.